Denial of Service: (DoS) Impact on Sensors - Daud, M; Rasiah, R; George, M; Asirvatham, D; Rahman, AFA; Ab Halim, A (IEEE, 2024)
IoT devices must provide seamless connectivity while meeting stringent power and size constraints. Network availability is a critical determinant of quality of service (QoS) delivered by the IoT System. This paper describes a series of simple experiments which study the impact of Denial of Service (DoS) on a IoT Sensor Node transmitting data to the cloud. The experiment will be used to develop future IoT Sensor Node implementation. The objective of this paper is to use experiments to unravel the negative impacts of DoS attacks on the IoT sensor nodes so as to place it on a strong research foundation. The results show that the impact of DoS is significant to IoT Sensor Node power consumption and network availability.